2017
DOI: 10.1016/j.trd.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Commute responses to employment decentralization: Anticipated versus actual mode choice behaviors of new town employees in Kunming, China

Abstract: This study examines workers" mode-choice responses to a typical job decentralization policy implemented in China"s urban developmentgovernment job relocation (GJR) to new towns in the urban periphery. Broadly, the literature suggests that job decentralization tends to increase car commuting; however, little is known about the effects of China"s GJR initiatives on individuals" commuting mode choices. Using Kunming as a case study, this study examines how workers" commuting mode choices have shifted in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…In ten studies (Aguiléra, Wenglenski, and Proulhac 2009; Bell 1991; Hanssen 1995; Meland 2007; Sprumont and Viti 2017; Vale 2013; Van Wee and Van Der Hoorn 2002; Walker, Thomas, and Verplanken 2015; Waygood, Kitamura, and Nakai 2007; Yang et al 2017), surveys were carried out before and after the relocation, while the rest of the studies used retrospective surveys or collected information through interviews with representatives of the companies or by reviewing the relevant planning documents. Some studies collected commute behavior information using a general classical travel survey, while others, such as (Hanssen 1995) and Sprumont and Viti (2017), collected commute mode choice information using a one-day and a two-week travel diary, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In ten studies (Aguiléra, Wenglenski, and Proulhac 2009; Bell 1991; Hanssen 1995; Meland 2007; Sprumont and Viti 2017; Vale 2013; Van Wee and Van Der Hoorn 2002; Walker, Thomas, and Verplanken 2015; Waygood, Kitamura, and Nakai 2007; Yang et al 2017), surveys were carried out before and after the relocation, while the rest of the studies used retrospective surveys or collected information through interviews with representatives of the companies or by reviewing the relevant planning documents. Some studies collected commute behavior information using a general classical travel survey, while others, such as (Hanssen 1995) and Sprumont and Viti (2017), collected commute mode choice information using a one-day and a two-week travel diary, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Some older studies mostly relied on descriptive analyses (Bell 1991; Daniels 1972, 1981; Wabe 1967), whereas some more recent studies had a focused research objective leading to a specific data collection process and less conventional methodological approaches (Sprumont and Viti 2017; Walker, Thomas, and Verplanken 2015; Yang et al 2017). Few studies used statistical models and exploited the data to identify the explanatory variables of the observed impacts on commuting behavior (Sprumont and Viti 2017; Sprumont et al 2014; Vale 2013; Yang et al 2017). Yang et al (2017) applied multinomial logit models, with revealed preference (RP) and stated preference (SP) data to explain the variation between anticipated and actual travel mode choice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al 2014; J. Yang 2010), increasing automobile usage, and discouraging nonautomobile travel modes (Wu, Wang, and Li 2018; X. Yang et al 2017).…”
Section: Scoping Review Of the Urban Structure–travel Relationship Inmentioning
confidence: 99%
“…The vast majority of literature concerning company relocation has been focused on movement away from the city centre to the suburbs or more general trends towards suburbanisation. This applies equally for studies performed outside of Norway ( [10][11][12][13][14][15][16][17][18][19]; Geographic Institute of Utrecht University 1990 in [20]) to those within Norway [21][22][23][24][25][26][27][28]. Common findings across all studies are increased car modal share typically a result of reduced public transport accessibility and favourable car parking allowances at the suburban location [17,20,23,27].…”
Section: Introductionmentioning
confidence: 99%